Reliability of prenatal detection of X‐linked hypohidrotic ectodermal dysplasia by tooth germ sonography - Hammersen, Johanna; Wohlfart, Sigrun; Goecke, Tamme W.; Köninger, Angela; Stepan, Holger; Gallinat, Ralph; Morris, Susan; Bücher, Katharina; Clarke, Angus; Wünsche, Stephanie; Beckmann, Matthias W.; Schneider, Holm; et al. (Prenatal diagnosis, 2019)
Objective In X‐linked hypohidrotic ectodermal dysplasia (XLHED), dysfunction of ectodysplasin A1 (EDA1) due to EDA mutations results in malformation of hair, teeth, and sweat glands. Hypohidrosis, which can cause life‐threatening hyperthermia, is amenable to intrauterine therapy with recombinant EDA1. This study aimed at evaluating tooth germ sonography as a noninvasive means to identify affected fetuses in pregnant carrier women. Methods Sonography, performed at 10 study sites between gestational weeks 18 and 28, led to the diagnosis of XLHED if fewer than six tooth germs were detected in mandible or maxilla. The assessment was verified postnatally by EDA sequencing and/or clinical findings. Estimated fetal weights and postnatal weight gain of boys with XLHED were assessed using appropriate growth charts. Results In 19 of 38 sonographic examinations (23 male and 13 female fetuses), XLHED was detected prenatally. The prenatal diagnosis proved to be correct in 37 cases; one affected male fetus was missed. Specificity and positive predictive value were both 100%. Tooth counts obtained by clinical examination corresponded well with findings on panoramic radiographs. We observed no weight deficits of subjects with XLHED in utero but occasionally during infancy. Conclusion Tooth germ sonography is highly specific and reliable in detecting XLHED prenatally. What is already known about this topic? In X‐linked hypohidrotic ectodermal dysplasia (XLHED), a developmental disorder characterized by malformation of hair, teeth, and sweat glands, inability to sweat can lead to life‐threatening hyperthermia. Hypohidrosis has been shown to be amenable to prenatal therapy. Tooth germ sonography may be used to detect fetal XLHED in pregnant carrier women but has not yet been evaluated in a broader setting. What does this study add? Tooth germ sonography is highly specific and reliable in detecting or ruling out fetal XLHED in pregnant carriers. Such sonographic assessments can be conducted in different countries at various sites representing different levels of care. This noninvasive method allows recognition of XLHED in time for possible prenatal therapy or prevention of dangerous hyperthermic episodes in early infancy.